The Application of the Use of Indonesian Language in Promoting Tourist Destinations to ArchipelagoTourists in North Toraja Regency - Ernawati AB; Syamsul Bahri; St. Aminah AB; Darmayasa (Pusaka : Journal of Tourism, Hospitality, Travel and Business Event, 2023)
Indonesian language should be encouraged through tourism promotion, especially in the tourism sector, to describe the form of tourism promotion and implementation. Bahasa Indonesia, as a domestic tourism promotion, also describes the role of Bahasa Indonesia as tourism communication to develop and internationalise Bahasa Indonesia in the Department of Tourism and Cultural of North Toraja Regency. This research aims to describe the tourism promotion form in the Department of Tourism and Cultural of North Toraja Regency. Data collection techniques with in-depth interviews through the Snowball Sampling technique for the stakeholder included the private management of tourism attractions, tour guide, and visitors at tourist destination areas. The conclusion of this research is the promotional language to use in the Department of Tourism and Cultural of North Toraja Regency through two options of language: Bahasa Indonesia and English language, but also uses a traditional or local vocabulary which is often used for tourist attraction and describe the local language.